Development of the Representation of the University Library in Social Networks - M. I. Abubakirova (Библиосфера)
The development of digitalization has led to increasing use of social networks by academic libraries as a means of marketing services. The literature review has shown that the purpose of library communications on social media is to persuade library users to pay attention to resources and services. Students, from their hand, perceive the library’s social media posts related to training support and publications about events at the university as most useful. Through social media, librarians try to develop relationships with their users. The problem is how to organize this work more effectively. The purpose of the article is to present the results of testing the program for the development of the library’s representative office in social networks. The development of resources is considered on the example of the university library group on the VKontakte social network. The interim results of the Program for three quarters are presented. Based on the presented data, positive dynamics of indicators is recorded and it is concluded that such an indicator as site traffic over time becomes more and more problematic, and work with user involvement in social networks requires great attention and different approaches from librarians. The results of the OKR marketing approach are of practical importance in managing the social networks of libraries of all forms of the organization.